2005
DOI: 10.1191/0269215505cr832oa
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of arm function assessment with standardized guidelines for the Fugl-Meyer Test, Action Research Arm Test and Box and Block Test: a multicentre study

Abstract: The standardized guidelines assured comparability of test administration and scoring across clinical facilities. The arm motor scales provided information that was not identical to information from the Hemispheric Stroke Scale or the Modified Barthel Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
541
3
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 733 publications
(565 citation statements)
references
References 20 publications
10
541
3
11
Order By: Relevance
“…As far as we know, most research on the concurrent validity and responsiveness of the FMA has looked at the upper extremity functions. Motion function was highly correlated with the action research arm test (ARAT) and the box and block test (r= 0.925 and 0.921, respectively) 18) , and van der Lee et al reported that intensive treatment for 22 chronic stroke patients' upper extremity functions gave a responsiveness ratio of 0.41 19) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, most research on the concurrent validity and responsiveness of the FMA has looked at the upper extremity functions. Motion function was highly correlated with the action research arm test (ARAT) and the box and block test (r= 0.925 and 0.921, respectively) 18) , and van der Lee et al reported that intensive treatment for 22 chronic stroke patients' upper extremity functions gave a responsiveness ratio of 0.41 19) .…”
Section: Introductionmentioning
confidence: 99%
“…The Jebsen-Taylor hand function test, the grip power test 10,11) , the Action Reach Arm Test (ARAT) 12) , the Berg Balance Scale (BBS) 13) , the Motor Assessment Scale (MAS) 14) , and the FMA 1) which include domains such as motor function and balance, sensation qualities, passive range of motion, and joint pain are the most widely used [15][16][17] . Research on the reliability and validity of the FMA has been conducted, but the majority of the research has only examined reliability and validity in one or two domains, not all the domains, or either of the upper or lower extremity 2,18,19) . Michaelsen et al reported that the FMA has a reasonable reliability for total motor scores of the upper extremity (ICC=0.98), lower extremity (ICC = 0.90), movement sense (ICC = 0.98), upper and lower extremities' passive range of motion (ICC=0.84 and 0.90, respectively), and tactile sensitivity (ICC =0.75) however, they had only evaluated the inter-rater reliability 20) .…”
Section: Introductionmentioning
confidence: 99%
“…Participants sat in front of a box, which was divided into two rectangles of the same area, and were asked to move as many 2.5 cm-sized wood blocks to the empty space as they could within 60 seconds. The test-retest reliability r was 0.98 [Chen, Chen, Hsueh, Huang, & Hsieh, 2009], and the inter-tester reliability [Platz, et al, 2005].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The BB consists of a box with a center partition [18][19][20]. Small wooden blocks were placed in one side of the box, and the subject was asked to use the prosthetic terminal device to grasp one block at a time, transport it over the partition, and release it.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Outcome measures of activity performance included four performancebased measures: the Modified Box and Block Test of Manual Dexterity (BB) [18][19][20], the Jebsen-Taylor Hand Function Test (JTHF) [21], the Activities Measure for Upper-Limb Amputees (AM-ULA) [22], the University of New Brunswick Test of Prosthetic Function for Unilateral Amputees (UNB) [23]; and two self-report measures: the Upper-Extremity Functional Scale (UEFS) from the Orthotics and Prosthetics Users Survey [24][25] and the Patient-Specific Functional Scale (PSFS) [26]. All performance-based measures were administered by OTs.…”
Section: Outcome Measuresmentioning
confidence: 99%